Akuntabilitas Pelayanan Publik di Desa Towuntu, Kecamatan Pasan, Kabupaten Minahasa Tenggara - Frangky Robial; Hendry Rumengan; Angely Sondakh; Mei Hastuti; Christian Tarandung; Rivaldi Kandou; Diana Wangania (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The aim of this research is to determine the implementation of public service accountability and the inhibiting and supporting factors in the implementation of public service accountability in East Towuntu Village, Pasan District. The approach in this research is qualitative descriptive research. This research was chosen because it presents data systematically, factually and accurately regarding the facts in the field. The object of this research is Public Services. This research was conducted at the Towuntu Village Office as an extension of the central government and provider of services to the community. The informants in this research were all Towuntu Village officials, Pasan District. In providing services to the community, the Towuntu Village Government has demonstrated performance accountability/accountability in order to maintain community trust. This is demonstrated by the existence of a flow of accountability starting from the lowest level, namely village officials, to their leaders, namely Old Law. There are several factors that can influence the accountability/accountability process, where these factors originate from within the individual as a Village Apparatus and the environmental influence of Towuntu Village. However, as the experience of Towuntu Village officials increases, the level of understanding of the importance of performance accountability can be increased so that the process of implementing accountability can run well.